PROTOTYPE SISTEM INFORMASI PERHITUNGAN NILAI POIN PELANGGARAN TATA TERTIB PADA SMK YUPPENTEK 1 TANGERANG - Himawan Himawan; Dede Cahyadi; Munawati Munawati (CCIT Journal, 2016)
creating a school atmosphere orderly and discipline is very important. Therefore is necessary to a regulation rules which would regulate the behavior patterns of students in the school. But with a growing pattern of student behavior, violation of school rules are common, especially in SMK Yuppentek 1 Tangerang. As a teacher in charge of providing services and counseling to students, it is the responsibility of counseling teachers to provide guidance to students with problems. Not many schools are aware of the importance of the use of information and communication technologies so that the process of recording and calculating the value of point offense, coaching up sanctions against students who violate the order was carried out with conventional systems. This resulted in the BK teachers takes a long time to handle students who have problems of having to create some bookkeeping records violation and fill the violation book manually so that the handling results are often invalid. In addition, delivery of information about good and bad behavior of students in the school to parents or guardians of students experiencing difficulties. In order to help the BK teacher performance, it needs to be made a system to calculate the point value rules violation at SMK YUPPENTEK 1 Tangerang. By using the methodology of research in the form of a SWOT analysis, it is expected that the system can simplify and accelerate the process of calculation of point offense, coaching until the sanctions to students who violate rules, and the delivery of information to parents or guardians of the student's behavior will be faster.In addition, principals can also find charts the level of discipline students based on grade level and department.